The effect of firing conditions on electrical conductivity and electrochemical properties of Sr0.8La0.2TiO3–Ce0.9Gd0.1O1.95 composite anodes for solid oxide fuel cells. Issue 2 (1st February 2016) - Koo, Ji-Hoon; Lee, Ki-Tae
Abstract: The electrical conductivity of Sr0.8 La0.2 TiO3 (SLT) increased significantly through reducing calcination and sintering processes. The electrical conductivity of SLT sintered three times under a reducing atmosphere was 249 S cm −1 at 800 °C in a H2 atmosphere, which is 40 times higher than that of SLT sintered in air. The enhanced electrical conduction might be caused by the variation in valence state from Ti 4+ to Ti 3+ . The single-cell performance of the Sr0.8 La0.2 TiO3 –Ce0.9 Gd0.1 O1.95 (SLT–GDC) composite anode improved with increasing amount of GDC. The SG (HHH)15 anode exhibited the highest maximum power density of 25 mW cm −2 at 800 °C for CH4 fuel.